Between Fact and Fabrication: How Visual Art Might Nurture Environmental Consciousness - Buening, Rebecca; Maeda, Takuya; Liew, Kongmeng; Aramaki, Eiji (Frontiers in Psychology, 2022)
Previous studies have highlighted the communicative limitations of artistic visualizations, which are often too conceptual or interpretive to enhance public understanding of (and volition to act upon) scientific climate information. This seems to suggest a need for greater factuality/concreteness in artistic visualization projects, which may indeed be the case. However, in this paper, we synthesize insights from environmental psychology, the psychology of art, and intermediate disciplines like eco-aesthetics, to argue that artworks--defined by their counterfactual qualities---can be effective for stimulating elements of environmental consciousness. We also argue that different artworks may yield different effects depending on how they combine counter/factual strategies. In so doing, we assert that effective artistic perceptualization--here expressed as affectivization---exceeds the faithful translation of facts from one mode to another, and cannot be encapsulated in a single example of un/successful art.